Розподіл поживних речовин у різних органах рослин генотипів Miscanthus Anderss. - Vergun, O.M.; Rakhmetov, D.B.; Rakhmetova, S.O.; Fishchenko, V.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2019)
Objective – to investigate the accumulation of biochemical compounds in the different organs of cultivars and varieties of Miscanthus Anderss. in conditions of M.M. Gryshko National Botanical Garden of the NAS of Ukraine. Material and methods. Investigated plants were cultivars and varieties of species of the genus of Miscanthus collected in an experimental collection of Cultural Flora Department of M.M. Gryshko National Botanical Garden of the NAS of Ukraine: М. × giganteus сv. Huliver (MGH), М. × giganteus f. ЕSBMG-3 (MGE-3), М. sacchariflorus сv. Snihopad (MSS), М. sacchariflorus f. ЕSMBS-3 (MSE-3), М. sinensis сv. Veleten (MSV), М. sinensis f. ESBMK-1 (MSE-1). The content of dry matter was determined according to A.I. Yermakov et al. (1972), the total content of sugars and ascorbic acid concentration – according to V.P. Krishchenko (1983), the content of carotene – according to B.P. Pleshkov (1985), the content of ash – according to Z.M. Hrycaenko et al. (2003), the content of calcium and phosphorus – according to H.M. Pochinok (1976). Energetic value of dry plant raw material determined on calorimeter. Results. In the period of full seed ripening the plant raw material of Miscanthus genotypes accumulated dry matter from 38.99 % (MSE-1, leaves) to 88.08 % (MSE-3, leaves), total content of sugars – from 2.72 % (MSE-3, panicles) to 10.03 % (MGH, stems), ascorbic acid – from 4.40 mg% (MSE-3, panicles) to 40.03 mg% (MGE-3, leaves), carotene – from 0.09 mg% (MSE-3, stems) to 0.26 mg% (MGH, leaves), ash – from 1.38 % (MSS, stems) to 8.65 % (MSV, leaves), calcium – from 0.19 % (MSS, stems) to 0.91 % (MGH, leaves), phosphorus – from 0.032 % (MGE-3, stems) to 0.412 % (MSE-3, panicles), protein – from 4.82 % (MSE-3, stems) to 12.28 % (MSE-1, leaves). Energetic value of dry raw was from 3811.87 cal/g (MSS, leaves) to 4193.17 cal/ g (MSV, panicles). Conclusions. Obtained data demonstrated that in conditions of M.M. Gryshko National Botanical Garden of the NAS of Ukraine cultivars and varieties of Miscanthus × giganteus, M. sacchariflorus, M. sinensis are the valuable source of nutrients and biofuel in the period of full seed ripening. Distribution of biochemical compounds in different organs resulted that accumulation of it depends on genotype. It was found that content of sugars was maximal and content of ash with macroelements, protein, carotene was minimal in the stems of investigated plants.